The Administration of Youth Justice Through the Lens of Community-Based Service Providers: Risk Factors and Programming Challenges - Rowan, Zachary R. (Canadian journal of criminology and criminal justice, 2024)
Since the Youth Criminal Justice Act of 2003 in Canada, the juvenile justice system has prioritized diverting youth away from in-custody sentences (incarceration in jail, prison, or other facilities) and towards a community-based system of justice. Despite this shift, there is limited research directly examining the experience of community-based service providers that were responsible for this shift in adjudicating youth. To understand the experience of working with youth involved in the system, we conducted semi-structured interviews with youth justice workers from one of the largest community-based organizations in a western Canadian province that offer alternatives to custody for at-risk youth. Findings provide a complex depiction of youth risk factors and illustrate the successes and challenges of administering youth justice in a community context.